RELEVANSI KEBUDAYAAN MASYARAKAT DESA GIRITENGAH DENGAN JAWA KUNO PADA RELIEF CANDI BOROBUDUR - Kharisma Nabila (Laboratorium Jurusan Arkeologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2023)
Giritengah Village is a village located about 6km to the southwest. Giritengah is a cultural village that has cultural diversity in the community. The culture in Giritengah village consists of local knowledge of the use of prey institutions for agriculture, traditional dances, arts, musical instruments, and traditional rituals of the community. The cultural diversity in Giritengah village cannot be separated from the cultural development of the past community. This paper aims to provide a complementary study of how the relevance of the Borobudur community occurred in the past and continues to the present in Giritengah village. This research data was obtained through literature study and participatory observation. This research uses a social archaeology approach, by reviewing the relevance or relationship between the current community relations in Giritengah village and the community depicted on the reliefs of Borobudur Temple. The results of this study explain that there are three aspects of relevance that exist in the Giritengah community, namely the social and cultural aspects, the flora aspect, and the art aspect of the Giritengah village community, all of which have relevance to the life of the ancient Javanese people in the reliefs of Borobudur Temple.